PENGARUH LIKUIDITAS, LEVERAGE DAN EFEKTIFITAS KOMITE AUDIT TERHADAP PREDIKSI FINANCIAL DISTRESS PADA PERUSAHAAN GO PUBLIC SEKTOR REAL ESTATE DAN PROPERTY TAHUN 2007-2009 : METODE ALTMAN Z-SCORE - M. Maulvi N.; M. Yasser Arafat (Fakultas Ekonomi, Universitas Negeri Jakarta, 2014)
The purpose is to know financial effectiveness in companies by using cash flow ratios as the tools of measurement. Research method that used is descriptive analysis, with collecting secondary data, searching data through library, cash flow analysis by using cash flow ratios and Trend From writing result can concluded that cash flow ratios could be the tools of measurement financial effectiveness and also could be a base and use for a making decision which can be used for next cash management case Key word: Effectiveness Financial, Cash Flow Ratios